Membedakan Perikarditis Konstriktif dan Kardiomiopati Restriktif dengan Menggunakan Alat Ekokardiografi: Membedakan Perikarditis Konstriktif Dan Kardiomiopati Restriktif dengan Gambaran Ekokardiografi - Savitri Sirait; Anna Fuji Rahimah (Jurnal Klinik dan Riset Kesehatan, 2026)
The clinical and hemodynamic features of Constrictive Pericarditis (CP) and Restrictive Cardiomyopathy (RCM) often overlap, making it difficult to differentiate and establish an accurate diagnosis. Both conditions are characterized by diastolic dysfunction, leading to symptoms such as dyspnea, fatigue, and peripheral edema. However, the underlying pathophysiology and management strategies of CP and RCM differ significantly, requiring an accurate diagnosis for appropriate management. Understanding the differences between CP and RCM is essential for effective patient management. Correct diagnosis influences treatment decisions. Constrictive Pericarditis is a reversible cause of heart failure, benefiting greatly from surgical pericardiectomy, while Restrictive Cardiomyopathy, rooted in permanent myocardial dysfunction, is managed primarily with supportive therapy. Echocardiography is established as the first-line imaging modality that can be used to treat these conditions. With the advancement of technology, the accuracy of diagnostic assessments of the features available from echocardiography has increased. Recent studies have validated conventional echocardiographic parameters that allow high sensitivity and specificity to differentiate CP and RCM. This literature review will combine several echocardiographic parameters that are important points in finding and assessing abnormalities arising from both diseases which will later facilitate analysis. The goal is to increase understanding of this condition among physicians and other health professionals in the field of imaging, which can ultimately improve diagnostic accuracy and more appropriate patient management. Continuous advances in echocardiographic techniques promise to improve outcomes and quality of life.